Réponse :
A = 4x² - 6x + 8 - 3x + 9x²
= 4x² + 9x² - 6x - 3x + 8
A = 13x² - 9x + 8
B = -8x² + 7x - 3 + 4x² - 9x + 11
= -8x² + 4x² + 7x - 9x - 3 + 11
B = -4x² -2x + 8
C = -4x + x² - 6 + 5x² + 3x - 10 - 8x² + 2x
= x²- 8x² + 5x² - 4x + 3x + 2x - 6 - 10
= -7x² + 5x² - x + 2x - 16
C = -2x² + x - 16
D = 2x² + 6x + x² - 3x - x² + 3x - 2x - 6x
= 2x² - x² + x² + 6x - 3x + 3x - 2x - 6x
D = 2x² - 2x
E = 9 - x² + 3x² - 9x + 7 + 5x³ - 7x³
= 5x³ - 7x³ - x² + 3x² - 9x + 7 + 9
E = -2x³ + 2x² - 9x + 13
F = 2x³ + 4 - 6x² + x² - 2x + 9x - 3x - 9x
= 2x³ - 6x² + x² - 2x + 9x - 3x - 9x + 4
F = 2x³ - 5x² - 5x + 4
Bon courage !
Si la réponse te plaît n'hésite pas de la marquer la réponse comme la meilleur !